Au jour le jour - cotidiano, moradia e trabalho em Belém (1890-1910) - Pantoja, Leticia Souto (2005)
This work aims to discuss the interstices present in the discourses of the press and of the public power concerning the city of Belém, in the turn of the 19th to the 20th century, a period in which the city lived under the impacts of the increment in the rubber export economy. It is considered that these discourses tried to project an image of the city in which the rich and the poor would be separated and antagonized not only due to economic, cultural, and social differences, but mainly due to spatial and dwelling distances. In this sense, supported by the presuppositions of social history, this study focuses on the analysis of the discourses formulated by Belém s daily newspapers and by the municipal legislation about poor workers and dwellers of slums, huts, and dirty eating-places. The work compares the meanings of these intellective formulations and the deriving political practices with the marks and signs left by the inhabitants in photographs, police occurrence reports and criminal proceedings. At the end, it is concluded that the city was not a mosaic of social spaces geographically distant from one another; in fact, it was a fluid social fabric, entangled by multiple territorialities and experiences which co-existed in the capital of the state of Pará, competing not only for spaces, but also for the construction of meanings about life in a city that wanted to consolidate itself as modern and advanced. Initially, the discourse of the local press and of the public power about the city of Belém is presented. The filter was the rich experience of the city and of its architecturally reformed spaces. Thus, the study approaches the values concerning nation, family and work owned by people coming from the segments that obtained gains from the latex export economy. It also analyzes some sociability practices and the good dwelling discourse constructed by these segments. Next, the work analyzes the discourse that the press and the legislative sources constructed about the public and private behaviors of the city s poor working class. In this perspective, the study discusses how members of the public power and activists from the local newspapers articulated discourses and campaigns against the forms of work, entertainment, affective relationships and dwelling habits of Belém s working class. After this, through the dialogue between judicial sources, the discourse of journalism and that of legislation, the work analyzes the interstices and breaches contained in the representations about the dwellers of collective habitations, such as huts and slums. In this case, the work reflects on judicial proceedings related to crimes that occurred in these types of dwellings, or to crimes whose involved parties lived in them. In the conclusion, photographs of several spaces of the city of Belém, produced between 1888 and 1910, are analyzed. The central objective was capturing the images of the city s modernity and progress. In the analysis of the backgrounds, penumbras, and corners of the photographs, the work gives visibility to the presence of poor workers in central spaces of Belém, in territories where it was attempted to hide their action and their daily survival practices.